Co-Relation of Hormonal Profile and BRCA1 in Sporadic Breast Carcinoma: A Single Institutional Experience of 303 Patients - Preeti Agarwal; Fatima Khan; Sameer Gupta; Shalini Bhalla; Ann Thomas; Akshay Anand; Kulranjan Singh; Abhinav Arun Sonkar (SAGE Publishing, 2022)
Introduction: Invasive Breast carcinoma-No special type (NST) is the most common breast malignancy accounting for 95% of breast cancers. Study of predictive and prognostic immunohistochemical markers estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (Her2neu) expression are crucial for treatment planning. Materials and Methods: In the present study we studied the hormonal profile in 303 sporadic breast cancers and BRCA1 protein expression in these patients along with its clinico-pathological correlation. Results: In our patient population, Triple negative Breast carcinoma (TNBC) (104/303; 34.3%) was the most common luminal subtype followed by Luminal A 74/303; 24.4%), Her2 enriched (65/303; 21.5%), and Luminal B (60/303; 19.8%) respectively. This contrasts with many western studies which commonly report Luminal A being the largest subgroup. BRCA1 protein loss was more prominently seen in TNBC (64/104;61.5%) highlighting the possibility that high grade tumors are more susceptible to some epigenetic modifications leading to higher likelihood of loss of BRCA1 protein. Conclusion: Hence, we conclude that like hereditary cases of breast carcinoma with BRCA1 mutation; BRCA1 loss is also more likely in sporadic TNBC cases.